Geographic Clusters of Primary Biliary Cirrhosis. Issue 2 (2003) - Abu-Mouch, Saif; Selmi, Carlo; Benson, Gordon D.; Kenny, Thomas P.; Invernizzi, Pietro; Zuin, Massimo; Podda, Mauro; Rossaro, Lorenzo; Gershwin, M. Eric
Abstract : Genetic and environmental factors have been widely suggested to contribute to the pathogenesis of primary biliary cirrhosis (PBC), an autoimmune disease of unknown etiology leading to destruction of small bile ducts. Interestingly, epidemiologic data indicate a variable prevalence of the disease in different geographical areas. The study of clusters of PBC may provide clues as to possible triggers in the induction of immunopathology. We report herein four such unique PBC clusters that suggest the presence of both genetic and environmental factors in the induction of PBC. The first cluster is represented by a family of ten siblings of Palestinian origin that have an extraordinary frequency of PBC (with 5/8 sisters having the disease). Second, we describe the cases of a husband and wife, both having PBC. A family in which PBC was diagnosed in two genetically unrelated individuals, who lived in the same household, represents the third cluster. Fourth, we report a high prevalence of PBC cases in a very small area in Alaska. Although these data are anedoctal, the study of a large number of such clusters may provide a tool to estimate the roles of genetics and environment in the induction of autoimmunity.